Enhanced light harvesting in GaAs thin-film solar cells using plasmonic gold (Au) nanoparticle absorbers. (2022) - Prashant, D.V.; Agnihotri, Suneet Kumar; Samajdar, D.P.
Abstract: Surface texturing methods are often used in thin-film solar cells (SCs) to achieve effective photon trapping. However, such approaches have a detrimental impact on cell performance and are not suitable for thin-films. Plasmonic light trapping using metal nanoparticles (NPs) is one of the promising technique for achieving superior optical absorption in thin-film SCs with less material usage. In this article, to improve the optical performance of GaAs thin-film SCs, a uniformly distributed Gold (Au) nanoparticle (NP) array is introduced at the top of transparent indium-tin-oxide (ITO) electrode. The Au NP array functions as an antireflection layer, increasing light harvesting in active layer for both visible and infrared (IR) wavelength regions. By performing 3-D finite-different time-domain (FDTD) analysis, we have presented a comparative optoelectronic study of the GaAs SCs with and without Au NPs. Photovoltaic parameters such as optical absorption (A (λ)), photogeneration density (Goptical rate), and photocurrent density (Jsc ) are used to evaluate performance of the structures. The proposed thin-film SCs with Au NPs achieved an optical absorption of 60% (planar) and 77% (NW array) with a remarkable photocurrent of 22.8 mA/cm 2 (planar) and 26.7 mA/cm 2 respectively.